Meta-Analysis of The Relationship Between Creative Thinking Ability and The Effectiveness of Creative Problem Solving Learning Model - Frans Sudirjo; Ade Suparman; Dody Tarihoran; Fredrik Warwer; Everhard Markiano Solissa (Departement of Mathematics Education, 2023)
Creative thinking ability is one of the skills of 4C (Critical Thinking, Creativity, Collaboration and Communication) that students must have. However, students' creative thinking skills are still quite low, so learning is needed that can improve students' creative thinking skills, one of which is by using a creative problem-solving learning model. This study aims to analyze the effect of creative problem-solving learning model on students' creative thinking skills, based on material, school level and region. The research used is quantitative research with meta-analysis method. This study used 16 articles and theses with a range of years 2013-2022. The sampling technique used was purposive sampling. Data were analyzed by coding and measuring effect size. The results found that the effect size of the creative problem-solving learning model on creative thinking skills was 1.32, which was in the very high category. Based on the material, there are nine materials with an effect size that shows the creative problem-solving model has a high influence. Based on school level, the effect size obtained in high school is 1.40 and in junior high school is 1.78. Based on region, there are nine provinces with an effect size that shows the creative problem-solving model has a high effect